Model of TSL-centers in Li₂B₄O₇:A (A = Cu, Ag) single crystals - Adamiv, V.T.; Antonyak, O.T.; Burak, Ya.V.; Pidzyrailo, M.S.; Teslyuk, I.M. (Functional Materials, 2005)
Basing on spectral studies of the transmission and thermostimulated luminescence of LТВ:А single crystals (А = Cu, Аg), a new mechanism has been proposed to explain the formation of TSL centers therein, so-called А⁰ centers, involving the growth defects of the foreign boron-oxygen complexes. The TSL emission occurs via the energy transfer to a self-localized exciton followed by emissive annihilation thereof.